2017
DOI: 10.2147/opth.s141771
|View full text |Cite
|
Sign up to set email alerts
|

Refractive changes after lens-sparing vitrectomy for macular hole and epiretinal membrane

Abstract: PurposeCataract progression after lens-sparing vitrectomy might differ according to original posterior segment diseases. Our objective was to analyze the refractive values after lens-sparing vitrectomy for macular hole (MH) and epiretinal membrane (ERM).Materials and methodsWe reviewed the medical records of 25 MH patients (25 eyes) and 23 ERM patients (23 eyes) who underwent lens-sparing vitrectomy. Refractive changes in both groups were compared. All patients underwent 20-gauge three-port pars plana vitrecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…The total refractive force of the eyeball was +58.64 D, including +43.05 D for the cornea and +16.0 -+20.0 D for the lens; thus, the vitreous has low refractive power. A relevant study reported that most of the progression of myopia after vitrectomy was linked to cataract progression (34). However, in the present study, no significant cataract progression was detected at 12 months post-operatively.…”
Section: Discussioncontrasting
confidence: 82%
“…The total refractive force of the eyeball was +58.64 D, including +43.05 D for the cornea and +16.0 -+20.0 D for the lens; thus, the vitreous has low refractive power. A relevant study reported that most of the progression of myopia after vitrectomy was linked to cataract progression (34). However, in the present study, no significant cataract progression was detected at 12 months post-operatively.…”
Section: Discussioncontrasting
confidence: 82%
“…Also, 23 G, 25 G, and 27 G instrumentation were introduced with advances in technology since 1971 (Fujii et al, 2002;Eckardt, 2005;Oshima et al, 2010). Many reports have described the development of nuclear cataract and refractive changes following lens-sparing vitrectomy (Ikeda et al, 2014;Okamoto et al, 2014;Muto et al, 2017). Also, some reports have found changes in refraction toward myopia in pseudophakic eyes who underwent 20 G and 23 G vitrectomy for various vitreoretinal pathologies (Suzuki et al, 2000;Akinci et al, 2008).…”
Section: Discussionmentioning
confidence: 99%